THE REPRESENTATION OF HEALTH MINISTER IN HANDLING COVID-19 IN INDONESIA: A CRITICAL DISCOURSE ANALYSIS - Yulia Anggraeni; Rosaria Mita Amalia (University of Muhammadiyah Malang, 2020)
COVID-19 outbreaks that threaten human health have become a pandemic. As the Health Minister in Indonesia, the actions were taken by the Letjen TNI (Purn) Dr. dr. Terawan Agus Putranto, Sp. Rad. (K) in handling this pandemic is in the spotlight. There are so many media that providenews related to the efforts of the Health Minister in handling this case, one of which is The Jakarta Post. This study aims to describe the representation of Mr. Terawan as Health Minister in handling COVID-19 cases in Indonesia in The Jakarta Post. Critical Discourse Analysis as an approach is used in his study. The data are the articles in The Jakarta Post related to Mr. Terawan in handling the COVID-19 cases in Indonesia. The data is analyzed using a discursive strategy. According to Wodak& Mayer (2001), there are five strategies in Discursive, but this study only applies two strategies, namely Nomination Strategies and Predication Strategies. The findings in this study are; (1) four nomination strategies areused by The Jakarta Post. They are deixis, proper names, professional anthroponym, and nouns. The Jakarta Post uses the nomination strategy to avoid repetition of the same proper name, to show the readers which person becomes the center of the text, and to describe and report Mr. Terawan’s action regarding his job as Health Minister; (2) The Jakarta Post gave a negative attribute to the performance of Mr. Terawan as a Health Minister in handling with COVID-19 cases.The Jakarta Post’s belief that Mr. Terawan has performed badly as a Health Minister in handling the COVID-19 case and The Jakarta Post sees Mr. Terawan as a careless person in the case.